Switching of Prescription Drugs to OTC Status at Benghazi Private Pharmacies - Antesar Boshhiha; Zahia Boshaiha; Sarah Alfirjani; Ameerah Amir; Sarah Ahmed (AlQalam Journal of Medical and Applied Sciences, 2022)
Background and objective. Over-the-counter drug (OTC) is a drug that is sold without a prescription to treat minor illnesses. The use of OTC medications has been repeatedly reported worldwide. This OTC use is increasingly marketed as part of self-medications. The purpose of the present study was to assess the pharmacist's role in switching from prescription drugs to OTC. Methods. A structured questionnaire comprised several questions distributed randomly to several pharmacists who worked at 44 private pharmacies in Benghazi, Libya. Data collected from questionnaires were analyzed by the SPSS program. Results. Throughout the study, the expert pharmacists were more proactive in the management of inappropriate OTC drugs use than pharmacists with a few years of experience. This might be authorized to improvements in communication skills of the experienced pharmacist and the ability to monitor the patients towards the aimed drugs. The patient's self-medication via the pharmacist was more controlled with the experienced pharmacist than the pharmacist with less experience. Conclusion. Considerable attention should be paid to the risks of the future expansion of inappropriate self-medication.